2008
DOI: 10.1007/s00122-008-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of cultivated soybean (Glycine max (L.) Merr.) landraces in China

Abstract: The Chinese genebank contains 23,587 soybean landraces collected from 29 provinces. In this study, a representative collection of 1,863 landraces were assessed for genetic diversity and genetic diVerentiation in order to provide useful information for eVective management and utilization. A total of 1,160 SSR alleles at 59 SSR loci were detected including 97 unique and 485 low-frequency alleles, which indicated great richness and uniqueness of genetic variation in this core collection. Seven clusters were infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
138
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(165 citation statements)
references
References 51 publications
15
138
4
1
Order By: Relevance
“…In addition, analyses of more samples are needed to probe how soybean subpopulations have adapted to different geographic areas 14 and to identify the large number of rare alleles that have been lost during soybean domestication and improvement 4 . These rare alleles could benefit future soybean improvement as they constitute excellent genetic variances, especially for resistant genes 4 .…”
mentioning
confidence: 99%
“…In addition, analyses of more samples are needed to probe how soybean subpopulations have adapted to different geographic areas 14 and to identify the large number of rare alleles that have been lost during soybean domestication and improvement 4 . These rare alleles could benefit future soybean improvement as they constitute excellent genetic variances, especially for resistant genes 4 .…”
mentioning
confidence: 99%
“…In fact, Vaz Patto et al (2009) found 12 private alleles in 54 populations of maize, which were evaluated using 13 microsatellite markers, whereas Bracco et al (2009) found 33 private alleles in six maize landraces using 10 microsatellite markers. According to Li et al (2008), rare SSR loci, especially in plants with rare alleles at multiple loci, may indicate that these landraces have had limited genetic exchange with other landraces, and therefore may have rare alleles for various functional traits as well. Because these unique or rare alleles are likely caused by natural mutation and selection (Mousadik and Petit, 1996), they can be used not only in the specific categorization of germplasm collections but also in breeding and plant development as unique markers (Li et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Microsatellite or simple sequence repeats (SSRs) markers has been used for genetic diversity analysis because microsatellites are plentiful variations over the genome and highly reproducible and easy for genotyping as a codominant markers. The high level of polymorphism was detected in several soybean collections; 18.3 alleles (6 microsatellite loci) in Korean soybean accessions (Yoon et al, 2009), 25.5 alleles (46 microsatellite loci) in wild soybean collection (Lee et al, 2008), 12.2 alleles (60 microsatellite loci) in Chinese soybean accessions (Wang et al, 2006), 19.7 alleles (59 microsatellite loci) in soybean landraces of China (Li et al, 2008). Using microsatellite markers, Choi et al (1999) analyzed the collection acquired from five major rivers in Korea and they supported that SSR markers are useful tool to classify cultivated soybeans and wild soybeans, and Dong et al (2004) analyzed genetic diversity of cultivated soybean accessions collected from several provinces of China and proposed one possible diversity center.…”
mentioning
confidence: 98%
“…Especially, landraces collected in center of origins are useful for genetic improvement of cultivars in that wild relatives generally reveal many unwanted traits and show low introgression rate (Song et al, 2013). Genetic analysis using molecular markers have been consistently studied to understand the genetic variability of soybeans, and have revealed the genetic structure and diversity of various soybean collections (Choi et al, 1999;Dong et al, 2004;Guan et al, 2010;Lee et al, 2008;Li et al, 2008;Wang et al, 2006;Yoon et al, 2009). Microsatellite or simple sequence repeats (SSRs) markers has been used for genetic diversity analysis because microsatellites are plentiful variations over the genome and highly reproducible and easy for genotyping as a codominant markers.…”
mentioning
confidence: 99%